2007
DOI: 10.2146/ajhp060256
|View full text |Cite
|
Sign up to set email alerts
|

Association between common asthma therapies and recurrent asthma exacerbations in children enrolled in a state Medicaid plan

Abstract: Children with asthma and insured by Medicaid were at a high risk of repeat exacerbations leading to increased hospitalizations and ED visits. Treatment with budesonide inhalation suspension in the first 30 days after a hospitalization or ED visit for asthma was associated with a significant reduction in the risk of repeat asthma-related hospitalizations or ED visits during the following year. Children who were adherent to their asthma controller medication had significantly lower odds of having a subsequent as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 32 publications
2
56
0
7
Order By: Relevance
“…BUKSTEIN [23] CAMARGO [22] HERNDON [26] ELKOUT [25] those who were less adherent [21][22][23]26]. RUST et al [21] (q=8) observed this protective effect only if adherence was measured as controller-to-total ratio.…”
Section: Objective Adherence Measurementsmentioning
confidence: 97%
“…BUKSTEIN [23] CAMARGO [22] HERNDON [26] ELKOUT [25] those who were less adherent [21][22][23]26]. RUST et al [21] (q=8) observed this protective effect only if adherence was measured as controller-to-total ratio.…”
Section: Objective Adherence Measurementsmentioning
confidence: 97%
“…Анализ историй болезни 10 896 детей с бронхи-альной астмой в возрасте до 8 лет (из них 6918 детей 4 лет и менее) показал, что применение будесонида через небулайзер (Пульмикорт ® суспензии) в тече-ние 12 мес после обострения заболевания значи-тельно снижает риск повторных обострений астмы по сравнению с использованием других схем терапии [32]. Включение небулизированного будесонида в те-рапию обострений бронхиальной астмы значительно улучшает функцию легких [33], а также способству-ет уменьшению сроков госпитализации при тяжелом обострении [34].…”
Section: мультитриггерная обструкция и диагностика бронхиальной астмыunclassified
“…Medication possession ratio (MPR) is one such measure used to calculate medication adherence. For the purposes of this study, MPR is calculated as the days of antiasthmatic medication supply dispensed divided by the number of days in the observation period (#365) minus the number of days in the hospital [22][23][24][25] . Previous studies have shown that medication adherence measurement for the entire study period, when used as a denominator, predicts hospitalization and healthcare costs in a more appropriate manner compared to adherence measures considering the period between the first and last refill [22,26,27] .…”
Section: Medication Adherencementioning
confidence: 99%